PENGETAHUAN IBU NIFAS TENTANG TANDA BAHAYA MASA NIFAS DI RSUD KARANGANYAR - Niken Bayu Argaheni; Lely Zubaidah (OVUM : Journal of Midwifery and Health Sciences, 2021)
Based on the Indonesian Demographic and Health Survey (IDHS), the maternalmortality rate (related to pregnancy, childbirth, and the postpartum period) is 359per 100,000 live births. After conducting a preliminary study at the KaranganyarRegional General Hospital, medical record data contained 9 incidents ofpostpartum hemorrhage and 1 incident of headache, epigastric pain, and blurredvision.This research uses a descriptive method. Sampling with nonprobability samplingtechnique accidental sampling type, the number of samples in this study were 30respondents. Data obtained by using a questionnaire and analysis usingunivariate analysis.knowledge of postpartum mothers about the danger signs during the postpartumperiod in Karanganyar Hospital was categorized as good as many as 14respondents (46.6%), sufficient knowledge as many as 11 respondents (36.6%),and lack of knowledge as many as 5 people (16.6%).The conclusion in this study was the knowledge of postpartum mothers inKaranganyar Hospital in the good category.